2019
DOI: 10.1002/term.2855
|View full text |Cite
|
Sign up to set email alerts
|

Keratin scaffolds with human adipose stem cells: Physical and biological effects toward wound healing

Abstract: Keratin, a natural biomaterial derived from wool or human hair, has the intrinsic ability to interact with different types of cells and the potential to serve as a controllable extracellular matrix that can be used a scaffold for tissue engineering. In this study, we demonstrated a simple and fast technique to construct 3D keratin scaffolds for accelerated wound healing using a lyophilization method based on extraction of keratin from human hair. The physical properties of the keratin scaffolds such as water u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 75 publications
(87 reference statements)
1
17
0
Order By: Relevance
“…In contrast, keratin is a family of fibrous proteins containing cell adhesion RGD sequences similar to fibronectin. In the form of 3D scaffolds produced by lyophilization method, keratin supported hADSCs adhesion, proliferation, and differentiation and the constructs were proved to shorten wound healing time and accelerate epithelialization in vivo [197]. Gelatin is a biopolymer product of either partial acid or alkaline hydrolysis of animal collagen.…”
Section: Scaffolds For Soft Tissue Applicationmentioning
confidence: 99%
“…In contrast, keratin is a family of fibrous proteins containing cell adhesion RGD sequences similar to fibronectin. In the form of 3D scaffolds produced by lyophilization method, keratin supported hADSCs adhesion, proliferation, and differentiation and the constructs were proved to shorten wound healing time and accelerate epithelialization in vivo [197]. Gelatin is a biopolymer product of either partial acid or alkaline hydrolysis of animal collagen.…”
Section: Scaffolds For Soft Tissue Applicationmentioning
confidence: 99%
“…Keratin dressings have been shown to accelerate wound closure and epithelialization possibly by enhancing the activation of keratinocytes in mice [91,92]. More recently, scientists found that the addition of human adipose stem cells to keratin scaffolds could further accelerate skin wound healing, re-epithelialization and tissue remodeling [93]. Together, the keratin scaffold represents a new natural biomaterial with great therapeutic potential for wound healing.…”
Section: Therapeutic Potential Of Keratins In Skin Diseasesmentioning
confidence: 99%
“…A host of fabrication techniques from electrospinning ( Wang et al., 2016d , 2016e ), wet spinning ( Yue et al., 2018 ), photomask micropatterning ( Yue et al., 2018 ), and compression molding/particulate leaching ( Katoh et al., 2004b ) to freeze casting of aqueous keratin solutions ( Lin et al., 2019 ; Tachibana et al., 2002 ) have been used to create keratin scaffolds. These scaffolds have many advantages, including a stable homogeneous, interconnected, porous structure ( Lin et al., 2019 ; Tachibana et al., 2002 ), free cysteine residues that can be used to bind bioactive substances to the scaffold surface ( Kurimoto et al., 2003 ; Tachibana et al., 2005 ), and resorbability ( Peplow and Dias, 2004 ) that make it a suitable material for tissue engineering and drug delivery ( Lin et al, 2017 , 2018 , 2019 ; Srinivasan et al., 2010 ; Verma et al., 2008 ). These properties have also led to studies on keratin-based biomaterials for wound ( Konop et al., 2017 ; Lin et al., 2018 ; Than et al., 2012 ; Wang et al., 2016d , 2016e ) and burn dressings ( Poranki et al., 2014 ).…”
Section: Keratin As a Materials For Engineered Systemsmentioning
confidence: 99%